If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -4x = -20 Reorder the terms: -4x + 2y = -20 Solving -4x + 2y = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -4x + 2y + -2y = -20 + -2y Combine like terms: 2y + -2y = 0 -4x + 0 = -20 + -2y -4x = -20 + -2y Divide each side by '-4'. x = 5 + 0.5y Simplifying x = 5 + 0.5y
| 2=20-2w | | -9-(-21)+(-24)-19= | | 3=9-3j | | X-8+2=0 | | 21b=2(4) | | 105+8x-4=14(5+2x)-9 | | 3b-14=4 | | 25X(x-5)= | | 38=47-v | | n=.6n+5.3 | | 54=43+x | | 9=-2+w | | 120-(4*150)= | | 5y-30=20 | | 7+2c=15 | | M+15=-15p | | 7+2c=1 | | V-6=-2 | | 5x+15-9=32 | | 120-(4*120)= | | 3x+12=36-5y | | 3x+19=10x+18 | | 2d-5=1 | | -5a=29 | | 13=7+2z | | 1+2t^3-3t^2=0 | | -4y+3=3x | | 4(x-9)-3=-5x+9(x+8) | | 3x^5-x^4-14x^3=0 | | 2x+3x+15-9=32 | | 41x+56=41x+48 | | 2-2x=4x-10 |